The effect of altering loading distance on skeleton start performance: Is higher pre-load velocity always beneficial?. Issue 17 (2nd September 2018) - Colyer, Steffi L.; Stokes, Keith A.; Bilzon, James L. J.; Holdcroft, Danny; Salo, Aki I. T.
ABSTRACT: Athletes initiating skeleton runs differ in the number of steps taken before loading the sled. We aimed to understand how experimentally modifying loading distance influenced sled velocity and overall start performance. Ten athletes (five elite, five talent; 67% of all national athletes) underwent two to four sessions, consisting of two dry-land push-starts in each of three conditions (preferred, long and short loading distances). A magnet encoder on the sled wheel provided velocity profiles and the overall performance measure (sled acceleration index). Longer pre-load distances (12% average increase from preferred to long distances) were related to higher pre-load velocity ( r = 0.94), but lower load effectiveness ( r = −0.75; average reduction 29%). Performance evaluations across conditions revealed that elite athletes' preferred distance push-starts were typically superior to the other conditions. Short loading distances were generally detrimental, whereas pushing the sled further improved some talent-squad athletes' performance. Thus, an important trade-off between generating high pre-load velocity and loading effectively was revealed, which coaches should consider when encouraging athletes to load later. This novel intervention study conducted within a real-world training setting has demonstrated the scope to enhance push-start performance by altering loading distance, particularly in developing athletes with less extensive training experience.